(untitled) (Damascus University Journal for the economic and Political sciences, 2024)
The research discussed the concept of buzz marketing and the impact of effective PR on Buzz marketing. The study conducted on a sample of 100 employees in the private and public banks in Syria. It also studied the effect of bank employees experience on the effectiveness of buzz marketing, and the differences of buzz marketing effectiveness among Syrian banks. The most important findings of the research: 1-There is an effect for public relations on buzz marketing. 2-There is an effect for publicity on buzz marketing. • There are statistically significant differences in the effectiveness of buzz marketing among banks. • There are statistically significant differences in the effectiveness of buzz marketing based on staff experience. • Highest level of effective buzz marketing was achieved by the category of 10 to 14 years of experience, followed by the one of 15-19 years of experience